2001
DOI: 10.1210/endo.142.11.8501
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Pancreatic β Cells from Intra-Islet Precursor Cells in an Experimental Model of Diabetes

Abstract: We previously reported that new beta cells differentiated in pancreatic islets of mice in which diabetes was produced by injection of a high dose of the beta cell toxin streptozotocin (SZ), which produces hyperglycemia due to rapid and massive beta cell death. After SZ-mediated elimination of existing beta cells, a population of insulin containing cells reappeared in islets. However, the number of new beta cells was small, and the animals remained severely hyperglycemic. In the present study, we tested whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 191 publications
(24 citation statements)
references
References 35 publications
3
20
0
1
Order By: Relevance
“…We previously showed that a dose of 200 mg/Kg of streptozotocin eliminated almost all the beta cells of islets a few hours after it was injected [8]. Few IN+ cells reappear in islets of hyperglycaemic (H) 7-day post-SZ mice (Fig.…”
Section: Insulin-dependent Increase In the Number Of Beta Cellsmentioning
confidence: 90%
See 4 more Smart Citations
“…We previously showed that a dose of 200 mg/Kg of streptozotocin eliminated almost all the beta cells of islets a few hours after it was injected [8]. Few IN+ cells reappear in islets of hyperglycaemic (H) 7-day post-SZ mice (Fig.…”
Section: Insulin-dependent Increase In the Number Of Beta Cellsmentioning
confidence: 90%
“…This antibody is highly specific for the nuclear form of Pdx-1. However, the high sensitivity of the confocal microscope allowed us to distinguish a weak cytoplasmic staining, which was not detected using a microscope with a conventional optical system [8].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations